Study of effects of PSB to paddy growth performance / Azwan Arifdin Abdul Wahid - Abdul Wahid, Azwan Arifdin (Faculty of Plantation and Agrotechnology, 2016)
Oryza sativa L. or commonly known as paddy or rice are the most essential and major grains commodity in the world. It has a very long journey of cultivation history. In paddy field, supplement inputs In harvest creation by roots are vital organ of plant to mineral sustenance. 17 supplements that fundamental for plant development as particle yet the accessible type of supplement in the dirt are constrained. Constrained measure of supplement in the dirt will limit the root development. Objectives of the study are to review on PSB effectiveness and to compare the effects of different PSB to paddy growth performance. The effects of root length and dry matter yield on paddy are compared with three types of phosphate solubilizing bacteria (PSB) between Bacillus, Pseudomonas and Rhizobium. The result for Pseudomonas and Bacillus were collected after 45 days and 60 days of sowing and Rhizobium is collected after 28 days. Pseudomonas gives the highest height with 92.30 cm followed by Bacillus with 80 cm. The plant heights for Rhizobium only 26.13 cm for 28 days, the possibility of seed to achieve the same height with Pseudomonas is low. In terms of dry matter yield, the highest result shown based on the Table 3 is the Bacillus with 21480 mg followed by Pseudomonas with 8780 mg and the lowest result is the Rhizobium with only 27.75 mg. Application of fertilizer needed in large quantity but nutrients uptake by plant just small in number. Plant growth regulator like PSB can be easily converted to substitute chemical application and this may become the advantages in future generation. The influence of PSB inoculation promising as biofertilizer since it can supply soluble form of phosphorus.